Evidence: Doing Justice - Levitt, Laura (Bulletin for the study of religion, 2012)
This brief essay explores what it means to consider the stuff in police storage and the physical remains of atrocity collected in Holocaust museums, libraries, and archives as the stuff of American Religious history. Moreover, the paper suggests how and in what ways these materials might enable scholars to do justice to traumatic pasts.